L’édition de manuels scolaires en langues régionales - Claire Torreilles (Lengas)
The round table allowed to exchange on the issues of pedagogical editing in Basque, Breton, Corsican and Occitan languages, to take stock of the existing structures and their functioning, to present the current editorial priorities. Although all projects are closely related to the CANOPÉ network, there are still significant historical disparities. But the debate showed convergences about the objectives: to favor the development of bilinguism, and about the transmission itself: methodological and linguistic reflection on the language to be taught.